Dermal open flow microperfusion for PK-based clinical bioequivalence studies of topical drug products - Birngruber, Thomas; Tiffner, Katrin I.; Mautner, Selma I.; Sinner, Frank M. (Frontiers in Pharmacology, 2022)
Topically applied drug products have experienced an extraordinary price increase in the USA, mostly due to a lack of generic products. Generic drug development is hindered by high costs and risks associated with clinical endpoint studies required to show bioequivalence (BE) of prospective generic products relative to their reference products. There is a continued need for cost- and time-efficient alternatives to clinical endpoint studies to determine BE of topically applied dermal drug products. Cutaneous PK-based BE studies present such an alternative and dOFM (dermal open flow microperfusion) has already been successfully used in several verifications studies to show an accurate and sensitive assessment of the rate and extent at which drugs become available in the skin. dOFM technology and the setup of clinical pilot and pivotal studies to achieve BE assessment with a minimum number of participants is discussed and an outlook is given on the use of dOFM technology for other drug products.